Body weight and psychological functioning in type 2 diabetes mellitus patients : a preliminary study - Pokrajac-Bulian, Alessandra (Array, 2018)
The aim of this study was to assess the relationship between beliefs about the causes of illness, glycaemic control, and affective status of overweight and obese women and men with type 2 diabetes. The clinical sample included 88 patients (46 males), aged from 31 to 79 years. Patients were examined in the Outpatient Clinic for Endocrinology, Diabetes and Metabolic Diseases in the Clinical Medical Centre Rijeka. Psychological measurements included the Revised Illness Perception Questionnaire and the Hospital Anxiety and Depression Scale. Patients' body weight, height and glycaemic control (HbA1c) were also obtained.The results show that body mass index (BMI) is not significantly correlated with the level of HbA1c, nor with measured psychological variables (psychological attributions of illness, anxiety and depressive symptoms). A stronger belief that illness was caused by psychological factors is correlated with more symptoms of anxiety and depression in patients. There was a significant main effect of patients' sex on psychological attributions and anxiety symptoms. Women reported stronger beliefs that psychological factors might have been the cause of their illness and showed higher levels of anxiety symptoms than men. There was no significant main effect of glycaemic control on measured psychological variables. The results suggest that in working with T2DM patients it is important to pay attention to psychological aspects of illness, taking into account the patient's sex. Inquiring about diabetes causation beliefs and emotional status may be a way of recognizing possible barriers towards providing care.